Az ösztöndíj-pályázathoz kapcsolódó kommunikációs szokások vizsgálata a z és y generáció tagjainak körében - Haffner-Kiss, Alexandra (Kultúratudományi Szemle, 2023)
In this study, I examine the applicant habits of members of the Z and Y generations and the relationship between the professional opportunities inherent in higher education scholarship applications from the perspective of applicants (students). Within this framework, I analyse the applicant's habits in the context of the lifestyle entwined by the information technology that also defines everyday life. Regarding the two generations, on the one hand, I am looking for answers to the questions of what can help increase the willingness to participate in tenders among the members of Generation Z; on the other hand, I also try to shed light on what effect the members of the Y generation thought they discovered in the development of their professional careers after the successful application.